PARASITIC NEMATODES ASSOCIATED WITH BAMBOO PLANTS -I. SPECIES OF HELICOTYLENCHUS FROM MANIPUR - MOHILAL, N.; DHANACHAND, CH.; ANANDI, Y. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2001)
<span style="color: #000000; font-family: Roboto, sans-serif; font-size: 13px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: justify; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">unvey of parasitic nematodes of Bamboo plants in Manipur revealed the occurrence of a large number of natodes belonging to the order Tylenchida. In this report eight known species of Helicotylenchus are corded. Helicotylenchus seshadrii and H. gramminophilus are being reported for the first time from Manipur.